A comparative analysis of the curriculum implemented in the village institutes - Ali Sinan Bilgili; Esra Mindivanli Akdoğan (Turkish History Education Journal)
Village Institutes were educational institutions in Türkiye that were structured in line with the educational, economic, social and political needs of the period. They constituted an important dimension of the works carried out to develop the country economically propagate the newly founded republic and its basic principles to the public. These institutions aimed to train well-equipped village teachers to develop the villages and the villagers in every aspect. The teachers who graduated from these institutions also shouldered the task of strengthening the bond between the village and the villagers and the state and the republic. The curriculum that determined the education process of the Village Institutes was first put into practice in 1943. Educational activities were carried out in line with the "education in work, education for work, education with work" principle. The students were active and educational activities were done holistically in these institutions. Furthermore, the students had the opportunity to apply the knowledge they had learned in the culture courses for themselves and in the agriculture courses through technical courses. However, in these educational institutions, the curriculum diverged partially from this aforementioned main principle after 1947. In the 1947 curriculum, which was revised in line with the criticisms made for the 1943 program, the agriculture and technical courses were reduced, and the culture courses were increased. With the 1953 Teacher Training Schools and Village Institutes curriculum, the five-year education increased to six years and the technical and agricultural courses were greatly reduced. Since the Village Institutes were closed in 1954, this curriculum could not be implemented for a long time. For this reason, it would not be wrong to state that the 1943 curriculum was the curriculum which that was developed and implemented in such a way as to fully meet the basic aims and principles of the Village Institutes.